Exploring public perceptions and support for green infrastructure funding mechanisms: a study of the Oxford–Cambridge Arc, England - Steadman, Shandelle; Smith, Heather M.; Jeffrey, Paul; Wheat, Phill (Taylor & Francis, 2023)
The uptake of green infrastructure is challenged by a lack of access to financing. Studies have investigated individuals’ economic valuation of green infrastructure but understanding public perceptions of a range of potential funding mechanisms is a fundamental step in developing funding measures. Using data collected from a sample of residents in the Oxford–Cambridge Arc, England, this study addresses a gap in our understanding of public perceptions of green infrastructure funding by investigating support for several funding mechanisms, and the extent to which support is associated with attitudinal, contextual and personal capability variables. Results indicate that respondents prefer the funding of small and large-scale infrastructure to be covered by developers, with most opposition being levelled at those involving additional financial obligations from citizens. Altruistic-biospheric values, pro-environmental behaviour and trust in the government significantly affected support. These findings provide valuable insight to policymakers attempting to introduce sustainable green infrastructure funding streams.
Keywords: green infrastructure; public perceptions; funding mechanisms